Icariin-loaded hydrogel with concurrent chondrogenesis and anti-inflammatory properties for promoting cartilage regeneration in a large animal model - Xu, Songshan; Zhao, Shaohua; Jian, Yanpeng; Shao, Xinwei; Han, Dandan; Zhang, Fan; Liang, Chen; Liu, Weijie; Fan, Jun; Yang, Zhikui; Zhou, Jinge; Zhang, Wenqiang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Currently, an effective repair method that can promote satisfactory cartilage regeneration is unavailable for cartilage damages owing to inevitable inflammatory erosion. Cartilage tissue engineering has revealed considerable treatment options for cartilage damages. Icariin (ICA) is a flavonoid component of Epimedii folium with both chondrogenic and anti-inflammatory properties. In this study, we prepared an ICA/CTS hydrogel by loading ICA into chitosan (CTS) hydrogel to impart chondrogenesis and anti-inflammatory properties to the ICA/CTS hydrogel. In vitro results revealed that ICA showed sustained release kinetics from the ICA/CTS hydrogel. In addition, compared to the CTS hydrogel, the ICA/CTS hydrogel exhibited a favorable in vitro anti-inflammatory effect upon incubation with lipopolysaccharide pre-induced RAW264.7 macrophages, as indicated by the suppression of inflammatory-related cytokines (IL-6 and TNF-α). Additionally, when co-cultured with chondrocytes in vitro, the ICA/CTS hydrogel showed good cytocompatibility, accelerated chondrocyte proliferation, and enhanced chondrogenesis compared to the CTS hydrogel. Moreover, the in vitro engineered cartilage from the chondrocyte-loaded ICA/CTS hydrogel achieved stable cartilage regeneration when subcutaneously implanted in a goat model. Finally, the addition of ICA endowed the ICA/CTS hydrogel with a potent anti-inflammatory effect compared to what was observed in the CTS hydrogel, as confirmed by the attenuated IL-1β, IL-6, TNF-α, and TUNEL expression. The prepared ICA/CTS hydrogel offered an effective method of delivery for chondrogenic and anti-inflammatory agents and served as a useful platform for cartilage regeneration in an immunocompetent large animal model.